PENGARUH SENAM YOGA MATA TERHADAP PENURUNANKELELAHAN MATA PADA PEKERJA DI DIVISI REDAKSI PADANG EKSPRES - Ratna Indah Sari Dewi; Vino Rika Novia (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2020)
Eye fatigue is a complaint that is often found on workers of computer users, because of an eye interaction with the continuous use of the computer and also the behavior of computer use that does not conform to Eye safety procedures. The purpose of this research is to learn about the influence of gymnastics yoga eye to eye fatigue on workers of computer users in the editorial division of Padang Express year 2019. This type of research is preexperimentation with the design used is One Group pretests posstest. The population amounted to 58 people and the number of samples of 16 computer users in the editorial division of Padang Ekspress taken with purposive sampling techniques. Data processed with computerised with univariate analysis using descriptive statistics and bivariate analysis using Wilcoxon test signed ranks test with a level of 95% significance.Results of univariate analysis, obtained average eye fatigue before the exercise of Yoga eye is 4.75 and after gymnastics namely 1.94. The results of bivariate analysis obtained no effect with the value P = 0,000 (P ≤ 0.05). Guided by the results of this study found that there is an effect of giving yoga eye exercises to eye fatigue in computer user workers. It is hoped to PT. Padang Intermedia Pers provides an education or briefing on eye safety procedures on workers of computer users, providing good lighting in the workspace by performing maintenance for lights that are extinguished or dull. In addition, it is advisable to do nonpharmacological therapy in overcoming eye fatigue in workers computer users, especially gymnastics yoga eyes. Keywords: eye fatigue, gymnastics Yoga eyesAbstrak : Kelelahan mata adalah keluhan yang sering ditemukan pada pekerja pengguna komputer, karena interaksi mata dengan penggunaan komputer yang terus menerus dan juga perilaku penggunaan komputer yang tidak sesuai dengan prosedur keselamatan mata. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh senam yoga mata terhadap kelelahan mata pada pekerja pengguna komputer di divisi redaksi Padang Express tahun 2019. Jenis penelitian ini adalah pra-eksperimen dengan desain yang digunakan One Group pretest posstest. Jumlah populasi 58 orang, sampel dari 16 pengguna komputer di divisi editorial Padang Express, dengan teknik purposive sampling. Data diolah dengan komputerisasi dengan analisis univariat menggunakan statistic deskriptif dan analisis bivariat dengan menggunakan uji Wilcoxon signed ranks test dengan tingkat signifikansi 95%. Hasil analisis bivariat berpengaruh dengan nilai P = 0,000 (P ≤ 0,05). Hasil penelitian ini ditemukan ada pengaruh pemberian latihan yoga mata terhadap kelelahan mata pada pekerja pengguna komputer. Diharapkan kepada PT. Padang Intermedia Press memberikan edukasi atau pengarahan tentang prosedur keselamatan mata pada pekerja pengguna komputer, memberikan pencahayaan yang baik di ruang kerja dengan melakukan perawatan untuk lampu yang padam atau pudar. Dan melakukan terapi non farmakologis dalam mengatasi kelelahan mata pada pekerja pengguna komputer, terutama mata yoga senam. Kata kunci : Mata lelah, Senam Yoga mata.